Evolution Law of Coal Seam Abutment Pressure under the Influence of Shallow Buried Complex Strata: A Case Study. (16th March 2021) - Zhang, Buchu; Sun, Dequan; Zheng, Ruiliang
Abstract : The evolution law of lateral abutment pressure under the condition of fully mechanized mining in shallow coal seam is studied using the change process of coal pillar stress in disturbed section as the research object. The results of physical simulation experiment show that, after coal mining, due to the collapse of coal seam roof, the overlying strata of key layer will disturb the section coal pillar to different degrees, and the sudden change of degrees of abutment pressure near the coal wall reaches the maximum. Affected by the energy released by the fracture of key stratum, the stress mutation area shifts to the coal wall at a deeper level and the range of plastic zone increases. From the perspective of the numerical simulation, according to the change characteristics of coal pillar abutment pressure in the mining process, the dynamic load process of complex roof strata is divided into three stages: the stage not affected by mining, the stage of dynamic load action, and the stage of static load. In the first stage, the lateral abutment pressure is only affected by the roadway mining, causing stress concentration in the coal body. The stress concentration coefficient is small, and the supporting stress is stable. In the second stage, with the advance of the working face, the coal seam load changes continuously owing to the movement of overlying rock in the goaf, and the lateral abutment pressure changes evidently under the influence of dynamic load. In the third stage, the overlying load forms stress concentration in the coal seam and continuously transfers to the coal wall at a deeper level, which increases the limit equilibrium area of coal body. During this period, the range of plastic zone still increases at a certain rate for a period of time and finally tends to be stable.